(753) The unified System Accounting in Czechoslovakia النظام الموحد للمحاسبة في تشيكوسلوفاكيا - Elhamy, Mohamed Adel (INP, 2024)
The government of the United Arab Republic is seeking to develop a unified accounting system to be used in the business sector, excluding banks and financial institutions. The Central Organisation of the Comptroller General of the United Arab Republic has issued a tentative unified accounting system and called on concerned enterprises to submit comments and suggestions in an effort to reach a practical and acceptable system. However, it seems there is a misunderstanding within the Central Organisation regarding the nature and elements of a unified accounting system. In our opinion, the proposed system appears to be a unified system of accounts rather than a unified accounting system. In an attempt to establish a scientific unified accounting system in the United Arab Republic, the Department of Financial Planning at the Institute of National Planning in Cairo is studying the experiences of other countries in using unified accounting systems, including the system implemented in Czechoslovakia, which was introduced on July 30, 1965, and became mandatory on January 1, 1966